The role of workers in transferring queen substances and the differences between worker castes in the leaf-cutting ant, Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) - Camargo, Roberto S. [UNESP]; Forti, Luiz Carlos [UNESP]; Lopes, Juliane F. S.; Andrade, Ana Paula P. [UNESP]; Raetano, Carlos Gilberto [UNESP]; Mendonça, Cristina G. [UNESP] (My University, 2006)
The present study focused on the relationship between the queen and workers in Acromyrmex subterraneus brunneus colonies mediated by the possible transfer of substances from the fertile to the sterile caste. The queens were submitted to different situations of physical limitation, i.e., they were kept isolated in cages with holes that only permitted the entry of workers but left the queen isolated. A tracer (water-soluble dye) was applied to the pronotum and gaster of the queen and its dispersal among workers was analyzed. The results demonstrated that the minor sub caste (0.7-0.9 mm) passed on the dye through allogrooming and self-grooming, or transferred the dye through trophallaxis to the major sub caste (1.2-2.0 mm) when they were not in direct contact with the queen. These findings indicate the communication and probable transfer of substances from the queen to the workers, as well as a substance transfer between workers.
Keywords: Allogrooming; Communication; Self-grooming; Acromyrmex subterraneus brunneus; Atta; Formicidae; Hymenoptera